Halogen bonding, hydrogen bonding and Lewis acidic receptors for anion recognition - Cornes, S (2016)
This thesis describes the preparation of acyclic, macrocyclic and interlocked receptors for the recognition of anions in competitive organic and aqueous solvent media. Chapter One introduces the field of anion supramolecular chemistry, with a particular focus on the non-covalent interactions used for anion recognition and the synthesis of mechanically interlocked molecules. Chapter Two discusses the preparation of halogen bonding and hydrogen bonding acyclic and interlocked pyridinium-based receptors. Investigations into their anion selectivity trends are undertaken using 1H NMR titration experiments. The anion sensing properties of analogous hosts containing a fluorescent quinolinium motif are also described. Chapter Three presents the synthesis of acyclic and macrocyclic receptors containing the dicationic 1,2-bis(pyridinium)ethane motif. Attempts towards the preparation of interlocked receptors containing the motif are also discussed. Chapter Four focuses on a series of water-soluble receptors based around functionalised α-cyclodextrins. Isothermal titration calorimetry experiments are used to investigate differences in the thermodynamics of anion binding to halogen bonding and hydrogen bonding analogues. Chapter Five details the preparation of a [2]rotaxane containing a Lewis acidic triarylborane motif. Investigations into its anion binding properties are conducted using multinuclear NMR and UV-visible spectroscopies. Chapter Six provides the experimental details and characterisation data for the compounds discussed in Chapters Two to Five. Protocols for the titration experiments conducted are also described. Full crystallographic data is provided in the Appendix.